Anesthetic management for cytoreductive surgery of pseudomyxoma peritonei with high intra-abdominal pressure: A case report - Lin, Yan-Jun; Lu, Liang-Yuan; Tao, De-Qiang; Yang, Zhan-Min (Frontiers in Surgery, 2023)
Anesthetic management for patients of pseudomyxoma peritonei (PMP) is challenging. This case report describes a patient of PMP with high intra-abdominal pressure. Intubation was performed in lateral position; the intraabdominal pressure was relieved slowly to prevent significant hemodynamic changes. Additionally, positive pressure ventilation was performed to reduce the risk of re-expansion pulmonary edema. During the operation, transfusion and infusion therapy was performed with target-mediated fluid therapy according to stroke volume variation (SVV) and cardiac index (CI) and blood gas analysis.